Auralización del sonido transmitido por vía aérea a través de dos adecuaciones diferentes para un tabique simple, considerando distintas locaciones de oyente (2017)
The design of the acoustic insulation of a building requires professional supervision during the planning and construction stages, the above because actually is necessary to guarantee an acoustic comfort that permit developed adequately activities with suitable background noise levels; for this some variables were considered such as the construction zone and the behavior of the different external sound sources that affect the façade, among others. This research proposes a method to auralize the noise that enters into an enclosure by air through one of the walls of the structure. The auralizations were obtained through the application of geometric acoustics models using CATT-Acoustics software and considering different source arrangements, several receiver points and two different adaptations for the facade of the room. The obtained auralizations for the evaluated receptor points show differences in the SPL and in the frequency content, however, it is necessary to analyze additional receiver points and compare the method proposed with measurements in real situations